The use of scientific and popular resources in the educational process - Petrushka, Alina (Видавництво Львівської політехніки, 2016)
In satisfying the information needs which are formed during studying students of universities and colleges the educational, scientific and popular programs transmitted through electronic and Internet media or other information resources primarily from the field of social and natural sciences can play a significant role. They have significant scientific, educational potential, which can be considerably interesting for youth. Popular science and educational segment in the Ukrainian mass media presented by research of the actual historical, political topics.
Keywords: audience; source; content; promotion; text